The Effectiveness of Artificial Intelligence–Based Videos in Improving the English Speaking Skills of Sixth-Grade Elementary School Students - Ika Sastrawati; Hilda Hafid (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Since traditional teaching techniques frequently offer few opportunities for active oral practice, the purpose of this study was to investigate the efficacy of employing an artificial intelligence (AI) application to enhance students' English speaking abilities. Two groups—an experimental group of 18 students and a control group of 16 learners—were used in the study's quasi-experimental design. To measure the students' speaking abilities both before and after the intervention, speaking pre-tests and post-tests were distributed to both groups. While the control group was instructed using traditional techniques, the experimental group was taught utilizing an AI-based application that enabled interactive speaking practice, pronunciation modeling, and continuous oral engagement. With the mean score rising from 59.14 on the pre-test to 81.47 on the post-test and 83.33% of students meeting the Minimum Mastery Criteria (KKM), the experimental group's speaking ability was found to have significantly improved. The control group, on the other hand, only slightly improved, with 37.50% of students meeting the KKM and mean scores rising from 58.62 to 66.38. These results show that incorporating artificial intelligence into English training improves students' speech performance, confidence, and engagement.